NILAI HETEROSIS DAN PERANAN INDUK PADA KARAKTER PERTUMBUHAN HASIL PERSILANGAN INTERSPESIFIK Tor soro DAN Tor douronensis - Deni Radona; Jojo Subagja; Irin Iriana Kusmini; Rudhy Gustiano (BERITA BIOLOGI, 2016)
Fish Tor is one of potential fish commodities to be developed because of their economic value. This on experiment was designed to evaluate the effect of male and female parent on morphological characters i.e length and weight growth and the value of heterosis from crosses of Tor soro and Tor douronensis. Crosses were performed in both directions (reciprocal) to form four populations. Observations lenght, weight gain, specific growth in length, specific growth in weight and value of heterosis were carried out for two months (January-March, 2014). The results showed an increase of  length, weight, specific growth in weight, specific growth in length occurred in seed produced from parent male of T. soro and female of T. douronensis with values of 0.54 cm, 0.09 g, 0.65 % and 3.79 %, rescpectively. Crossed of ? T. douronensis x ? T. soro yield heterosis value (partial) of length (40.90%) and weight (116.66%) was higher than crossed of ? T. soro x ? T. douronensis  that only have heterosis value of 0 and 33.33 %, and heterosis value (reciprocal) on the length of 20.45 % and the weight of 45.22 %.